2013
DOI: 10.1049/iet-its.2012.0151
|View full text |Cite
|
Sign up to set email alerts
|

Application of global positioning system and questionnaires data for the study of driver behaviour on two‐lane rural roads

Abstract: ABSTRACT:Methodologies based on naturalistic observation provide the most accurate data for studying drivers' behaviour. This paper presents a new methodology to obtain naturalistic data related to drivers' behaviour in a road segment. It is based on the combination of using global positioning system data and drivers' questionnaires. The continuous speed profiles along a road segment and the characteristics of drivers, of their trips and the type of their vehicles can be obtained for a great amount of drivers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Teniendo en cuenta que el control sobre el recorrido realizado por los mismos y sus condiciones de circulación fueron mínimas, es necesario estudiar cada uno de estos perfiles para garantizar que se incluyen en el estudio únicamente aquellos circulando en flujo libre. La metodología utilizada para la evaluación de las condiciones de circulación en flujo libre ha sido la desarrollada por Pérez-Zuriaga et al (2013). Está basada en la hipótesis de que cada conductor se comporta de una forma particular, aproximándose su perfil de velocidad individual al de un percentil.…”
Section: Fig 1 -Tipo De Vehículos Utilizados En El Estudiounclassified
“…Teniendo en cuenta que el control sobre el recorrido realizado por los mismos y sus condiciones de circulación fueron mínimas, es necesario estudiar cada uno de estos perfiles para garantizar que se incluyen en el estudio únicamente aquellos circulando en flujo libre. La metodología utilizada para la evaluación de las condiciones de circulación en flujo libre ha sido la desarrollada por Pérez-Zuriaga et al (2013). Está basada en la hipótesis de que cada conductor se comporta de una forma particular, aproximándose su perfil de velocidad individual al de un percentil.…”
Section: Fig 1 -Tipo De Vehículos Utilizados En El Estudiounclassified
“…Those speed measurements were obtained by means 134 of video recording, far away from drivers' line of sight. Results showed that drivers were no biased by the presence of 135 GPS devices Pérez-Zuriaga et al 2013). 136 37 tangent-to-curve transitions were identified from those ten road segments.…”
Section: Methodsmentioning
confidence: 93%
“…This selection was carried out after 138 an in-depth analysis of the operating speed profiles for all drivers. Vehicles travelling at non-free-flow conditions were 139 also discarded from the analysis (Pérez-Zuriaga et al 2013). The number of vehicles at each tangent-to-curve 140 transition ranged from 24 to 102.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations